THE AFRICAN PROVERB AND THE LIVING PRESENT: A PARADIGM FROM RECENT IGBO PAREMIOLOGY - Nwachukwu-Agbada, J.O.J. (Proverbium - Yearbook, 2012)
Modernity, the triptych upon which a corpus of Igbo sayings has been created, arose pari passu with the larger incidence of post-colonialism. As a phenomenon with a pervasive grip on the life and imagination of the African, post-colonialism has had its imprint on Igbo paremiology. Thus where the events out of which the Igbo paremiographer forged his/her sayings had taken place in the colonial era, it is safe to state that the coinage proper was likely to have been a post-colonial engagement since proverb formulation takes place long after the experience(s). It is then easy to observe a set of emergent saws which evidently show they are re-cent, and therefore ‘modernist.’ Such sayings are the outcome of the con-tact between Africa and the West as well as the power of the prevailing air of modern globalization sweeping across the continents. In this paper, we identify two subgenres of the Igbo proverb tradition, each of which evokes newness. The first category bears proverb terms which are unambiguously alien to the Igbo language vocabulary while the second is couched in a code-switch of Igbo and English, and which again readily flaunts its modernist credentials. Ordinarily, the proverb is associated with ancientness, with established custom and tradition, but the aphorisms in question are new, vibrant and audacious in rendition, and prove rather decisively that in Africa proverb-minting and usage remain an ongoing folkloric agenda.